PELAKSANAAN PENILAIAN PEMBELAJARAN TEMATIK DI SD PURWANTORO 1 KOTA MALANG DAN MI NURUL ISLAM TAJINAN KABUPATEN MALANG - Dyah Worowirastri Ekowati (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2014)
Educational assessment standards were prepared in order to complete the assessment standards. This study aims to describe the ability of teachers in assessment of thematic learning. Based on the results of the research, which shows the performance evaluation based on the curriculum 2013, has not been fully implemented by Shanta 1 SD Negeri Malang and MI Nurul Islam sub district of Tajinan. The obtained data will be very useful for determining measures or policies relating to the assessment standards, which in turn is expected to improve the quality of the school. Keywords: Assessment, Thematic Learning